CHILDHOOD NON-LANGERHANS CELL HISTIOCYTOSIS - AN ATYPICAL CASE - Coelho, Sandrina (2016)
Introduction: Histiocytoses correspond to a heterogeneous group of disorders characterized by the proliferation and infiltration of histiocytes in tissues. For years, many of the histiocytoses where known by numerous names, reflecting the lack of understanding regarding their origin.Case report: A previously healthy, 4-month-old infant presented a cutaneous lesion of progressive growth on his nose since 1 month ago. The mother has a diagnosis of Sjögren syndrome. On examination, there was a firm well- -defined erythematous plaque with 30 mm of diameter and raised edges, on the bridge of the nose. At the left cheek, left thoracic region and right arm there were also small erythematous papules with 5 days of evolution. The analytical study showed elevated antinuclear antibodies and anti-SS-A. Histopathological examination confirmed the diagnosis of non-Langerhans cells histiocytosis. Progressively, more annular erythematous papules and plaques appeared scattered over the face, trunk and limbs with spontaneous resolution of the first lesion on the nose. About 2 months after the initial evaluation, all lesions had regressed spontaneously, with normalization of analytical study at one year-old.Conclusion: Many authors believe that the different subtypes of histiocytosis represent only different stages of the same disease. Immunophenotyping of histiocytosis does not always identify the subtype involved, making the occurrence of atypical cases frequent.